(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
“Life well spent is long”, is well stated by Leonardo Da Vinci. A person’s quality of life throughout all of those years of survival, rather than how many years they live, is what defines a long-life span. Superior constitution, great bodily components, excellent soul, adoption of a wholesome diet, and living a healthy lifestyle are the factors of this longevity. The lifespan of the individual should be checked by the doctor before any other aspects such as ailment, season, bio-fire, age, mental agility, homologation, constitution, medication, and location are examined. The attributes of Deerghayu that is long life span, along with Aahara (eating habits) and vihara (routines) to preserve longevity of life with the highest quality, have been outlined by Acharya Charaka after the Namakarana (naming ceremony) and Sushruta in Jatisutriya adhyaya in their description of life span. The present study analyzes the characteristic features of Deerghayu and the maintenance of these characteristics playing an important role in a long and healthy life.